2019
DOI: 10.1111/mec.15113
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence of genetic variation with pleiotropic effects on caterpillar fitness and plant traits in a model legume

Abstract: Plant–insect interactions are ubiquitous, and have been studied intensely because of their relevance to damage and pollination in agricultural plants, and to the ecology and evolution of biodiversity. Variation within species can affect the outcome of these interactions. Specific genes and chemicals that mediate these interactions have been identified, but genome‐ or metabolome‐scale studies might be necessary to better understand the ecological and evolutionary consequences of intraspecific variation for plan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 106 publications
(142 reference statements)
1
34
0
Order By: Relevance
“…Our results suggest that adult weight and development time had a polygenic basis in the BC mapping populations, with a lack of major effect loci, except perhaps for weight in BC-L2. A polygenic architecture is not unexpected given the quantitative and complex nature of weight and development time, and similar results have been observed in other systems (e.g., [13,85]). We found negative correlations between effect estimates for adult weight and development time, such that SNPs associated with increased weight were also associated with slower development (consistent with [62]).…”
Section: Genetics Of Performance Traitssupporting
confidence: 82%
See 3 more Smart Citations
“…Our results suggest that adult weight and development time had a polygenic basis in the BC mapping populations, with a lack of major effect loci, except perhaps for weight in BC-L2. A polygenic architecture is not unexpected given the quantitative and complex nature of weight and development time, and similar results have been observed in other systems (e.g., [13,85]). We found negative correlations between effect estimates for adult weight and development time, such that SNPs associated with increased weight were also associated with slower development (consistent with [62]).…”
Section: Genetics Of Performance Traitssupporting
confidence: 82%
“…All of these metrics integrate (via MCMC) over uncertainty in the effects of individual SNPs, including whether these are non-zero. Using this BSLMM approach, it is also possible to obtain genomic-estimated breeding values (GEBVs), that is, the expected trait value for an individual from the additive effects of their genes as captured by both β and the polygenic term [12,13].…”
Section: Multilocus Genome-wide Association Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…Predicting evolutionary response by M. sativa would of course depend on a genetic understanding of the relevant plant traits, which the present study does not include. However, a recent study of M. melissa performance on a related plant, Medicago truncatula , found that genetic variation in the plant explained a substantial proportion of phenotypic variation (between 8% and 57%) in phytochemical and structural traits but also in caterpillar performance (Gompert et al, 2019). Of course, most plants do not have the luxury of optimizing defense against a single herbivore, and it is easy to imagine that improvements in defense against one enemy could lead to increased attraction to another (Salazar et al, 2018), especially given the diversity of effects even within major classes studied here, including saponins and phenolic glycosides.…”
Section: Discussionmentioning
confidence: 99%